The influence of replacing fish meal partially in diet with soybean meal and full-fat soya on growth and body composition of rainbow trout (oncorhynchus mykiss) - Harlío?lu, Ayşe Gül (My University, 2011)
Rainbow trouts were fed for five months with iso-nitrogenous (average 50.36 % crude protein) diets in which dietary protein was supplied by fish meal (FM), soybean meal (SBM) or full-fat soya (FFS). Diet 1 (control diet) contained 43% FM and 25% SBM. Those of experimental diets were 28% FM and 40% SBM for Diet 2, 13% FM and 55% SBM for Diet 3, 28% FM and 40% FFS for Diet 4, and 13% FM and 55% FFS for Diet 5, respectively. It was found that an increase in plant protein in diets adversely affected growth performance and feed conversion ratio (FCR) in rainbow trout. It was also found that the fish fed with the diet containing FFS had significantly higher FCR than the fish fed with SBM (P<0.05). In comparison control diet to fish fed with Diet 2 and 3 there were no significant differences (P>0.05) in body protein content. In addition, the lowest cost to produce 1 kg fish can be obtained from experimental Diet 2. There was not a significant (P>0.05) difference in specific growth rate, protein efficiency ratio, protein productive value, lipid productive value, energy productive value and FCR between control diet and Diet 2, and SBM can be used up to 40% in rainbow trout growth rations. In conclusion, this study showed that Diet 2 is optimum for rainbow trout. Copyright 2011 Zoological Society of Pakistan.
Keywords: Full fat soy bean meal; Growth; Nutrition; Oncorhynchus mykiss; Rainbow trout; Soy bean meal